Population Pharmacokinetics of Rituximab in Pediatric Patients With Frequent-Relapsing or Steroid-Dependent Nephrotic Syndrome - Chen, Yewei; Shen, Qian; Dong, Min; Xiong, Ye; Xu, Hong; Li, Zhiping (Frontiers in Pharmacology, 2021)
Objectives: Rituximab (RTX) is frequently used off-label for the treatment of frequent-relapsing nephrotic syndrome (FRNS) or steroid-dependent nephrotic syndrome (SDNS), but the relapse rate remained high and the dosing regimen varied widely. The objective of this study was to characterize RTX pharmacokinetics (PK) in pediatric patients with FRNS/SDNS, and to investigate the differences in RTX PK between patients with FRNS/SDNS and other disease populations. Methods: Fourteen pediatric patients received rituximab for FRNS/SDNS treatment were enrolled in a prospective, open-label, single-center PK study. A population PK model of RTX was developed and validated, and PK parameters were derived for quantitative evaluation. Results: A two-compartment PK model best described the data. Body surface area was the most significant covariate for both central clearance (CL) and apparent central volume of distribution (V1). Patients with FRNS/SDNS exhibited a clinically relevant increase in RTX CL compared to patient population with non-Hodgkin’s lymphoma (NHL). Conclusions: This pilot study indicated that higher doses or more frequent regimens of RTX may be required for optimal therapeutic effects in patients with FRNS/SDNS. Further clinical studies with more patients are warranted to confirm this result.